1976
DOI: 10.1126/science.818709
|View full text |Cite
|
Sign up to set email alerts
|

Chloramine Mutagenesis in Bacillus subtilis

Abstract: Chloramine (which occurs widely as a by-product of sanitary chlorination of water supplies) is shown to be a weak mutagen, when reversion of trpC to trpC in Bacillus subtilis is used as an assay. Some DNA-repair mutants appear to be more sensitive to chloramine, suggesting the involvement of DNA targets in bactericide. The influence of plating media on survival of cells treated with chloramine suggests a bacterial repair system acting upon potentially lethal lesions induced by chloramine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Alternative proposals for killing mechanisms have invoked various consequences of sulfhydryl oxidation (13,26,44), cell envelope alteration (4,33,39), or nucleotide dysfunction (45,46 (47)(48)(49) unless incubated with the microbes for several hours (13). Because chloramines derived from endogenous amines show this same behavior (8,13), their role in physiological disinfection processes is probably minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative proposals for killing mechanisms have invoked various consequences of sulfhydryl oxidation (13,26,44), cell envelope alteration (4,33,39), or nucleotide dysfunction (45,46 (47)(48)(49) unless incubated with the microbes for several hours (13). Because chloramines derived from endogenous amines show this same behavior (8,13), their role in physiological disinfection processes is probably minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis upon HOCl exposure has been investigated in studies using various tester strains of Salmonella typhimurium (51,55), with contradictory results. Chloramines were reported to be mutagenic in S. typhimurium and in Bacillus subtilis (45,51). Epidemiological studies concluded that there is a relationship between an increased risk of bladder cancer (40) and colorectal cancer (18) and drinking chlorinated water.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that HOCl can attack DNA (55). A few reports have shown that chloramine, which can be generated in vivo by HOCl (10,49), causes DNA damage (10,44,45,51), and genotoxicity of free chlorine and chloramines in drinking water was detected with amphibians (27). Recently, Candeias et al (12) have shown that in vitro, hypochlorous acid can also directly generate hydroxyl radicals via a Fenton-type reaction (24) (9).…”
mentioning
confidence: 99%
“…In particular, HOCl reacts with NH 4 ϩ and organic amines to form highly toxic chloramines, which also are strong oxidizing and chlorinating compounds and could be the actual killing agents. These chloramines are very diffusible species that can enter cells through membranes and react with intracellular components, including DNA (10,32,33,35).In studies of plant-bacterium interactions, it is sometime necessary to use monoxenic models in which a surface-sterilized plant is associated with a bacterial strain. Oxidative agents like household bleach, which is composed of sodium hypochlorite, are the agents most commonly used for sterilization.…”
mentioning
confidence: 99%
“…In particular, HOCl reacts with NH 4 ϩ and organic amines to form highly toxic chloramines, which also are strong oxidizing and chlorinating compounds and could be the actual killing agents. These chloramines are very diffusible species that can enter cells through membranes and react with intracellular components, including DNA (10,32,33,35).…”
mentioning
confidence: 99%